Developing performance indicators of the guidance componments - Po, Fernando Tan 1947- (1987)
The aim of the study is to operationalize a pre-post evaluation scheme to validate five program areas in an ongoing guidance program in the Division of City Schools in Manila. The study seeks to determine whether the indicators developed can be used for evaluation of the guidance program. The indicators are: improvement in grades, improved behavior which is comprised of reduced absenteeism and reduction of disciplinary problems, improved decision making and improved interpersonal relationship.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita
Keywords: Personnel service in secondary education; Counseling